A study of the sign reversal from a transmission peak to an absorption dip in a V-type system using the D1 and D2 lines of 87Rb in the presence of a buffer gas. (2nd November 2022) - Dey, Sekhar; Das, Chandan; Bhattacharyya, Dipankar; Ray, Biswajit
Abstract: In this work, we have investigated the transmission peak and absorption dip in the Doppler broadened V-type system using the D1 and D2 lines of 87 Rb atoms in the presence of nitrogen buffer gas. The effects of the probe power variations at a fixed pump power on these resonances are examined both experimentally and theoretically. We have explored the fact that the transmission peak essentially turns into an absorption dip when the probe power is stronger than the pump power. Moreover, the theoretical model of a five-level V-type system is found to be sufficient to support the experimental outcomes when the effect of collision due to the presence of buffer gas is included in the theoretical model. We have also shown the variation of the resonance amplitude and population distribution in the upper level (|5〉) with increasing probe power.